FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMSI MAKAN BUAH DAN SAYUR PADA ANAK PRA SEKOLAH PAUD TK SAPTA PRASETYA KOTA SEMARANG - Nurmahmudah, Diah Kartika; Aruben, Ronny; Suyatno, Suyatno (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Fruits and vegetables are the common of foodstuffs wich are easily found. They are such kind of necessity wich significant for all family members. Based from WHO advisory, there are found 31% for heart disease and 11% for stroke disease in the world because of less consumption of fruits and vegetables inside the body. The objective of this study is to know what factors which are affecting the behavior of fruits and vegetables sonsumption for the children. The variables of the study are Predisposing Factor, which contains of children nutrion education and behaviour. Second is Enabling Factors, wich contains of nutrion education in school and avaibility of fruits and vegetables and last Reinforcing Factors, wich contains of mass media and family. By using the qualitative study/more showing about the perspective subject, the data collection was done by using questionaire, interviewing to the informant directly, and the sample is 8 childrens and triangulation informant contains of parent informant and the learner. The results from correlation of Predisposing factor showed that the necessity of fruits and vegetables consumption was still under WHO recommendation 66,6-166,6 g/days to 200-300 g/days. In Reinforcing factor, there was not a correlation between mother education with fruits and vegetables consumption. Lastly, the result of Enabling factors was the availability about nutrient education at school, the availability of fruits and vegetables in daily consumption and the earnings wich is affecting fruits and vegetables availability. For each family members are suggested to consume fruits and vegetables everyday in order to fulfill the nutrient in family.